Mobile interact: uma ferramenta de auxílio didático proporcionando interação entre professores e alunos através de celulares - Dantas, Kaio Alencar de Azevedo (2010)
Education is one of the oldest activities practiced by man, but today it is still performed often without creating dialogues and discussions among all those involved, and students are passives agents without interactivity with teachers and the content approached. This work presents a tool used for providing interactivity in educational environments using cell phones, in this way, teachers can use technology to assist in process of education and have a better evaluation of students. The tool developed architecture is shown, exposing features of wireless communication technologies used and how is the connection management using Bluetooth technology, which has a limited number of simultaneous connections. The details of multiple Bluetooth connections and how the system should behave by numerous users are displayed, showing a comparison between different methods of managing connections. Finally, the results obtained with the use of the tool are presented, followed by the analysis of them and a conclusion on the work